2006
DOI: 10.1097/01.hjh.0000244953.62362.41
|View full text |Cite
|
Sign up to set email alerts
|

Ambulatory arterial stiffness index and renal abnormalities in primary hypertension

Abstract: Increased AASI is independently associated with early signs of renal damage in patients with sustained primary hypertension. These results strengthen the usefulness of AASI and ambulatory blood pressure monitoring in cardiovascular risk assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
59
1
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(69 citation statements)
references
References 22 publications
5
59
1
3
Order By: Relevance
“…Nonetheless, recent studies have suggested that AASI has a prognostic value even beyond traditional risk factors. [6][7][8]33,34 Thus, evaluation of AASI could become an important diagnostic tool, provided further clinical and experimental studies confirm and ultimately validate it.…”
Section: Discussionmentioning
confidence: 97%
“…Nonetheless, recent studies have suggested that AASI has a prognostic value even beyond traditional risk factors. [6][7][8]33,34 Thus, evaluation of AASI could become an important diagnostic tool, provided further clinical and experimental studies confirm and ultimately validate it.…”
Section: Discussionmentioning
confidence: 97%
“…1,2 A measure of this linear relationship, derived from ambulatory BP monitoring (ABPM), the Ambulatory Arterial Stiffness Index (AASI), 3 was recently shown to be associated with the metabolic syndrome, 4 with early signs of renal damage 5 and with other target organ damage 6 in patients with hypertension. In addition, AASI predicted prognosis, including cardiovascular and stroke mortality, 7,8 as well as stroke (but not cardiovascular events).…”
Section: Introductionmentioning
confidence: 99%
“…Crosssectional studies in hypertensive subjects have shown that AASI is related with renal abnormalities, increased carotid intimamedia thickness and left ventricular hypertrophy. [5][6][7] However, 24-h pulse pressure, a simple surrogate measure of arterial stiffness that reflects the static difference between SBP and DBP, without considering the variability in their relationship, was better than AASI in predicting progression of albuminuria in elderly patients with type 2 diabetes. 8 AASI was found to predict an increased risk of cardiovascular mortality in a mixed cohort of hypertensive and normotensive patients.…”
Section: The Linear Relationship Between Sbp and Dbp: A New Marker Ofmentioning
confidence: 99%